A Maquete como recurso didático para o ensino-aprendizagem de conceitos geográficos - Cassemiro, Rodrigo Rosa [UNESP] (2014)
The biggest challenge faced by teachers in the area is thinking about teaching practices that favor closer relationship between geographical concepts and social practices of students. Therefore, the objective of the research was to investigate the approach about the use of the model as a didactic resource on geography class, through the analysis, the proposal was to develop models that allow interactivity, in other words, that facilitate the student the manipulation of objects in a smaller scale, as an auxiliary element in teaching- learning process. Furthermore, it was also examined if this resource contributes to the learning of various geographical concepts of difficult assimilation, such as the organization of urban space, the relief shapes and cartographic orientation. The research was based primarily on a detailed study of the proposals made by Rosangela Doin de Almeida (2006 ), and partnership among Maria Elena Ramos Simielli, Gisele Girardi and Rosemeire Morone (2007). Thus, it seeks to establish new parameters of the model use, trying to insert either elements already used before or new ways of using this didactic resource